Relationship Between Leaflets and Root in Normal Aortic Valve Based on Computed Tomography Imaging: Implication for Aortic Valve Repair - Yang, Tianyang; Wen, Haini; El-Hamamsy, Ismail; Ni, Qiming; Sun, Yanbin; Zhu, Dan (Frontiers in Cardiovascular Medicine, 2021)
Objective: By assessing the normal dimensions and the relationship between the aortic root and leaflets in Chinese population, the objective of this three-dimensional computed tomography (3DCT)-based study was to establish a matching reference for leaflets and aortic root for aortic valve (AV) repair. Method: Electrocardiogram-gated multi-detector CT was performed on 168 Chinese participants with a normal aortic valve. Measurements of the aortic annuli and leaflets were obtained. The correlations between and the ratios of the specific root and leaflet measurements were analyzed. The references for the leaflet and root dimensions were suggested based on geometric height (gH) using a linear regression equation. The utility of the ratios was tested with CT images of 15 patients who underwent aortic valve repair. Result: The mean annulus diameter (AD), sino-tubular junction (STJ) diameter, geometric height (gH), effective height (eH), free margin length (FML), commissural height (ComH), inter-commissural distance (ICD), and coaptation height (CH) were 22.4 ± 1.7 mm, 27.3 ± 2, 0.4 mm, 15.5 ± 1.7 mm, 8.9 ± 1.2 mm, 32.0 ± 3.4 mm, 17.9 ± 1.9 mm, 23.1 ± 2.3 mm, and 3.1 ± 0.6 mm, respectively. The gH/AD, FML/ICD, and eH/ComH ratios were 0.69 ± 0.07, 1.38 ± 0.08, and 0.50 ± 0.07, respectively. The gH correlated with all other leaflet and root measurements (P < 0.01), whereas the FML demonstrated a better correlation with ICD compared with gH (R2 = 0.75, and R2 = 0.37, respectively). The FML/ICD and eH/ComH ratios might be used to assess leaflet-root mismatch and post-repair leaflet billowing. Conclusion: The normal aortic valve measurements based on 3DCT revealed a specific relationship between the root and leaflets; and this will guide the development of an objective method of aortic valve repair.